Manifestations of femininity in Mahmoud Fahmy's drawings (Al-Academy, 2023)
This tagged research deals with the manifestations of femininity in Mahmoud Fahmy's drawings by studying and monitoring the presence and how women were represented in the drawings of the artist Mahmoud Fahmy. Through the drawings of the expatriate Iraqi artist, Mahmoud Fahmy, in highlighting the manifestations of beauty for women, which constitute a formal characteristic that appears through the body, and Fahmy depicts it in an atmosphere of realism at times and magical realism at other times, as the research consists of four chapters. Through the following question: Did femininity appear in the drawings of the artist Mahmoud Fahmy? The importance of the research is that it sheds light on the manifestations of femininity in the drawings of this artist.The theoretical framework dealt with two sections, the first talks about the concept of femininity and the female in the ancient and contemporary arts, and the second section dealt with the artist Mahmoud Fahmy and his artistic style while coming up with indicators for this theoretical framework. From the artist's drawings, and the research concluded with the results and conclusions, including:1. The woman's body and her femininity is the primary inspiration and basis for the focus of the work. It is the hero of the story and its inspiration for the artistic themes of the artist Mahmoud Fahmy.2. Heritage, belonging, originality, place and neighborhoods are important characteristics of the artist Mahmoud Fahmy.3. In addition to the conclusions, recommendations and proposals to reach the goal of the research, which is to identify the manifestations of femininity in Mahmoud Fahmy's drawings.